Damage Control Surgery for Thoracic Outlet Vascular Injuries: The New Resuscitative Median Sternotomy Plus Endovascular Aortic Balloon Occlusion of the Aorta Approach (Colombia Medica, 2021)
Thoracic vascular trauma is associated with high mortality and is the second most common cause of death in patients with trauma following head injuries. Less than 25% of patients with a thoracic vascular injury arrive alive to the hospital and more than 50% of these die within the first 24 hours. Thoracic trauma with the involvement of the great vessels is a surgical challenge due to the complex and restricted anatomy of these structures and its association with adjacent organ damage. The aim of this article is to delineate the experience obtained in the surgical management of thoracic vascular injuries via the creation of a practical algorithm that includes basic principles of damage control surgery. We have been able to show that the early application of a resuscitative median sternotomy together with Zone I resuscitative endovascular balloon occlusion of the aorta (REBOA) in hemodynamically unstable patients with thoracic outlet vascular injuries improves survival by providing rapid stabilization of central aortic pressure and serving as a bridge to hemorrhage control. Damage control surgery principles should also be implemented when indicated followed by definitive repair once the correction of the lethal diamond has been achieved. To this end, we have developed a six-step management algorithm that illustrates the surgical care of patients with thoracic outlet vascular injuries according to the American Association of the Surgery of Trauma (AAST) classification.